Fondasi Etika Marketing : Analisis Tafsir Tematik dan Istinbath Hukum Surat Ali Imran Ayat 133, 134 dan 159 - Ulwan, Nasih; Bisri, Hasan; Athoillah, Muhamad (Sharia Journal and Education Center Publishing, 2025)
The concept of marketing in the Islamic perspective is not always aimed solely at achieving profit, but also takes into account ethical values, spirituality, and social responsibility. This article aims to analyze the concept of Islamic marketing based on Surah Ali Imran verses 133, 134, and 159, with an emphasis on business ethics, leadership, and social interaction. This study uses a qualitative method with a library research approach, through thematic interpretation analysis (tafsir maudhu‘i) and istinbāṭ al-ḥukm with the ushul fiqh framework. The primary data sources are the Qur'an and classical and contemporary tafsir books, while the secondary data includes literature on Islamic economics and Islamic marketing. The results show that QS. Ali Imran verse 133 emphasizes the principles of healthy competition and speed in doing good as the basic ethos of Islamic marketing, verse 134 contains the values of generosity, emotional control, and forgiveness as the foundation of social business ethics, while verse 159 emphasizes gentle leadership, deliberation, and tawakkal as principles of Islamic marketing management and communication. The results of the study show that QS. Ali Imran verse 133 emphasizes the principles of healthy competition and speed in doing good as the basic ethos of Islamic marketing, verse 134 contains the values of generosity, emotional control, and forgiveness as the foundation of social business ethics, while verse 159 emphasizes gentle leadership, deliberation, and tawakkal as principles of Islamic managerial and marketing communication. This discussion confirms that these three verses form a normative framework for sharia marketing that integrates spiritual, moral, and professional dimensions. Thus, Islamic marketing in the perspective of the Qur'an is not merely a marketing strategy, but a practice of muamalah oriented towards benefit, justice, and blessing.